Bis(2-diphenylphosphinoxynaphthalen-1-yl)methane: transition metal chemistry, Suzuki cross-coupling reactions and homogeneous hydrogenation of olefins - Punji, Benudhar; Mague, Joel T.; Balakrishna, Maravanji S. (Dalton Transactions, 2006)
Transition metal complexes of bis(2-diphenylphosphinoxynaphthalen-1-yl)methane (1) are described. Bis(phosphinite) 1 reacts with Group 6 metal carbonyls, [Rh(CO)2Cl]2, anhydrous NiCl2, [Pd(C3H5)Cl]2/AgBF4 and Pt(COD)I2 to give the corresponding 10-membered chelate complexes 2, 3 and 5–8. Reaction of 1 with [Rh(COD)Cl]2 in the presence of AgBF4 affords a cationic complex, [Rh(COD){Ph2P(–OC10H6)(µ-CH2)(C10H6O–)PPh2-κP,κP}]BF4 (4). Treatment of 1 with AuCl(SMe2) gives mononuclear chelate complex, [(AuCl){Ph2P(–OC10H6)(µ-CH2)(C10H6O–)PPh2-κP,κP}] (9) as well as a binuclear complex, [Au(Cl){µ-Ph2P(–OC10H6)(µ-CH2)(C10H6O–)PPh2-κP,κP}AuCl] (10) with ligand 1 exhibiting both chelating and bridged bidentate modes of coordination respectively. The molecular structures of 2, 6, 7, 9 and 10 are determined by X-ray studies. The mixture of Pd(OAc)2 and 1 effectively catalyzes Suzuki cross-coupling reactions of a range of aryl halides with aryl boronic acid in MeOH at room temperature or at 60 °C, giving generally high yields even under low catalytic loads. The cationic rhodium(I) complex, [Rh(COD){Ph2P(–OC10H6)(µ-CH2)(C10H6O–)PPh2-κP,κP}]BF4 (4) catalyzes the hydrogenation of styrenes to afford the corresponding alkyl benzenes in THF at room temperature or at 70 °C with excellent turnover frequencies.

Derivatisation and transition metal chemistry of a new monophosphinite ligand: 2-(diphenylphosphinoxy)naphthyl - Punji, Benudhar; Balakrishna, Maravanji S. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2006)
Reaction of monophosphinite ligand, 2-(diphenylphosphinoxy) naphthyl, C10H7PPh2 (1) with elemental sulphur or selenium gives the corresponding sulphide C10H7OP(S)Ph2 (2) or selenide C10H7OP(Se)ph2 (3) derivatives. Reaction of 1 with [CpRu(PPh3)2Cl] gives monosubstituted complex, [CpRu(C10H7OPPh2)(PPh3)C1] (4) as well as the disubstituted complex. [CpRu(C10H7PPh2)2Cl] (5) depending upon the reaction conditions. Treatment of 1 with [Rh(CO)2Cl]2 affords a trans-complex, [Rh(CO)(C10H7PPh2Cl] (6). Reaction of 1 with [Pd(COD)Cl2] results in the formation of an unexpected chlorobridged dipalladium complex: [Pd (PPh2O)( PPh2OH)(μ-Cl)]2 (7), whereas similar reaction with [pt(COD)Cl2] gives cis-[Pt(C10H7PPh2)2Cl2] (8) in good yield.

Ruthenium(II), copper(I) and silver(I) complexes of large bite bisphosphinite, bis(2-diphenylphosphinoxynaphthalen-1-yl)methane: Application of Ru(II) complexes towards the hydrogenation of styrene and phenylacetylene - Punji, Benudhar; Mague, Joel T.; Balakrishna, Maravanji S. (Journal of Organometallic Chemistry, 2006)
Ruthenium(II), copper(I) and silver(I) complexes of large bite bisphosphinite Ph2P{(-OC10H6)(μ-CH2)(C10H6O-)}PPh2 (1) are described. Reactions of bisphosphinite 1 with [Ru(η6-p-cymene)(μ-Cl)Cl]2 and RuCl2(PPh3)3 afford mono- and bis-chelate complexes [RuCl(η6-p-cymene){η2-Ph2P{(-OC10H6)(μ-CH2)(C10H6O-)}PPh2-κP,κP}]Cl (2) and trans-[RuCl2{η2-Ph2P{(-OC10H6)(μ-CH2)(C10H6O-)}PPh2-κP,κP}2] (3), respectively. Treatment of 1 with CuX (X = Cl, Br and I) furnish 10-membered chelate complexes of the type [Cu(X){η2-Ph2P(-OC10H6)(μ-CH2)(C10H6O-)PPh2-κP,κP}] (4, X = Cl; 5, X = Br; 6, X = I), whereas [Cu(MeCN)4]PF6 affords a bis-chelated cationic complex [Cu{η2-Ph2P(-OC10H6)(μ-CH2)(C10H6O-)PPh2-κP,κP}2][PF6] (7). Reaction between 1 and AgOTf produce both mono- and bis-chelated complexes [Ag{η2-Ph2P(-OC10H6)(μ-CH2)(C10H6O-)PPh2-κP,κP}(SO3CF3)] (8) and [Ag{η2-Ph2P(-OC10H6)(μ-CH2)(C10H6O-)PPh2-κP,κP}2][SO3CF3] (9), respectively; whereas the similar reaction of 1 with[Ag(OTf)PPh3] affords chelate complex of the type [Ag{η2-Ph2P(-OC10H6)(μ-CH2)(C10H6O-)PPh2-κP,κP}(PPh3)(SO3CF3)] (10). All the complexes were characterized by 1H NMR, 31P NMR, elemental analysis and mass spectrometry, including low-temperature NMR studies in the case of silver complexes. The molecular structures of 4 and 6 are determined by X-ray diffraction studies. Ruthenium complexes 2 and 3 promote catalytic hydrogenation of styrene and phenylacetylene with good turnover numbers.

Suzuki cross-coupling reactions catalyzed by palladium complex of an inexpensive phosphinite, 2-diphenylphosphinoxynaphthyl - Punji, Benudhar; Ganesamoorthy, Chelladurai; Balakrishna, Maravanji S. (Journal of Molecular Catalysis A-Chemical, 2006)
A facile and less expensive monophosphinite ligand 2-(diphenylphosphinoxy)-naphthyl, C10H7OPPh2 (1) has been synthesized from the reaction of β-naphthol with chlorodiphenylphosphine. The mixture of Pd(OAc)2 and 1 catalyzes the Suzuki cross-coupling of a variety of aryl halides with aryl boronic acids at room temperature or at 60 °C, giving generally high yields even under low catalytic loads. The effect of solvent, base and catalyst loading on the coupling reaction of aryl halide with arylboronic acid is also described.

Synthesis of neutral (PdII, PtII), Cationic (PdII), and water-induced anionic (PdII) complexes containing new mesocyclic thioether-aminophosphonite ligands and their application in the suzuki cross-coupling reaction - Punji, Benudhar; Mague, Joel T.; Balakrishna, Maravanji S. (Inorganic Chemistry, 2006)
Mesocyclic thioether−aminophosphonite ligands, {−OC10H6(μ-S)C10H6O−}PNC4H8O (2a, 4-(dinaphtho[2,1-d:1‘,2‘-g][1,3,6,2]dioxathiaphosphocin-4-yl)morpholine) and {−OC10H6(μ-S)C10H6O−}PNC4H8NCH3 (2b, 1-(dinaphtho[2,1-d:1‘,2‘-g][1,3,6,2]dioxathiaphosphocin-4-yl)-4-methylpiperazine) are obtained by reacting {−OC10H6(μ-S)C10H6O−}PCl (1) with corresponding nucleophiles. The ligands 2a and 2b react with (PhCN)2PdCl2 or M(COD)Cl2 (M = PdII or PtII) to afford P-coordinated cis-complexes, [{(−OC10H6(μ-S)C10H6O−)PNC4H8X-κP}2MCl2] (3a, M = PdII, X = O; 3b, M = PdII, X = NMe; 4a, M = PtII, X = O; 4b, M = PtII, X = NMe). Compounds 2a and 2b, upon treatment with [Pd(η3-C3H5)Cl]2 in the presence of AgOTf, produce the P,S-chelated cationic complexes, [{(−OC10H6(μ-S)C10H6O−)PNC4H8X-κP,κS}Pd(η3-C3H5)](CF3SO3) (5a, X = O and 5b, X = NMe). Treatment of 2a and 2b with (PhCN)2PdCl2 in the presence of trace amount of H2O affords P,S-chelated anionic complexes, [{(−OC10H6(μ-S)C10H6O−)P(O)-κP,κS}PdCl2](H2NC4H8X) (6a, X = O and 6b, X = NMe), via P−N bond cleavage. The crystal structures of compounds 1, 2a, 2b, 4a, and 6a are reported. Compound 6a is a rare example of crystallographically characterized anionic transition metal complex containing a thioether−phosphonate ligand. Most of these palladium complexes proved to be very active catalysts for the Suzuki−Miyaura reaction with excellent turnover number ((TON), up to 9.2 × 104 using complex 6a as a catalyst).

Group 11 metal complexes of mesocyclic thioether-aminophosphonites, (-OC10H6) - Punji, Benudhar; Mague, Joel T.; Balakrishna, Maravanji S. (European Journal of Inorganic Chemistry, 2007)
Group 11 metal complexes of the mesocyclic thioether aminophosphonites [-OC10H6(μ-S)C10H6O-]PNC4H8E {2a: E = O; 2b: E = NMe; IUPAC names: 4-(dinaphtho[2,1-d:1′,2′-g][1,3,6,2]dioxathiaphosphocin-4-yl)morpholine (2a), 1-(dinaphtho[2,1-d:1′,2′-g][1,3,6,2]dioxathiaphosphocin-4-yl)-4-methylpiperazine (2b)} are reported. Thioether aminophosphonites 2a and 2b react with CuX (X = Cl, Br, and I) in a 1:1 molar ratio to give the tricoordinate, dimeric complexes [{[{-OC10H6(μ-S)C10H6O-}PNC4H8E-κP]Cu(μ-X)}2] (4a: E = O, X = Cl; 4b: E = NMe, X = Cl; 5a: E = O, X = Br; 5b: E = NMe, X = Br; 6a: E = O, X = I; 6b: E = NMe, X = I), whereas with 2:1 molar ratios monomeric complexes of the type[{[-OC10H6(μ-S)C10H6O-]PNC4H8O-κP}2CuX] (7a: E = O, X = Cl; 7b: E = NMe, X = Cl; 8a: E = O, X = Br; 8b: E = NMe, X = Br; 9a: E = O, X = I; 9b: E = NMe, X = I) are obtained in excellent yield. The P,S-chelated cationic complexes[{[-OC10H6(μ-S)C10H6O-]PNC4H8E-κP,κS}2Cu]BF4 (10a: E = O; 10b: E = NMe) are obtained when 2a and 2b are treated with half an equivalent of [(MeCN)4Cu]BF4. Similarly, thesilver complexes [{[{-OC10H6(μ-S)C10H6O-}PNC4H8E-κP,κS]AgCF3SO3}2] (11a: E = O: 11b: E = NMe) and [{[-OC10H6(μ-S)C10H6O-]PNC4H8E-κP,κS}Ag(PPh3)]CF3SO3 (12a: E = O; 12b: E = NMe) are synthesized by the treatment of thioether aminophosphonites 2a and 2b with AgOTf and [Ag(PPh3)][OTf], respectively. Reactions of 2a and 2b with [AuCl(SMe2)] produce the simple monomeric gold(I) complexes [{[-OC10H6(μ-S)C10H6O-]PNC4H8E-κP}AuCl] (13a: E = O; 13b: E = NMe). The iodo derivatives [{[-OC10H6(μ-S)C10H6O-]PNC4H8E-κP}AuI] (14a: E = O; 14b: E = NMe) are obtained by the halide-exchange reaction of 13a and 13b with CuI at room temperature. The structures of complexes 5a, 7a, 8a, 13a, 13b, and 14a are confirmed by single-crystal X-ray diffraction studies. In all of these complexes, the sulfur atom in the mesocyclic ring shows coordinative interaction towards the phosphorus atom, and in 5a, 7a, 8a, and 14a towards the metal center as well. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007)

Highly air-stable anionic mononuclear and neutral binuclear palladium(ii) complexes for C−C and C−N bond-forming reactions - Punji, Benudhar; Mague, Joel T.; Balakrishna, Maravanji S. (Inorganic Chemistry, 2007)
The short-bite aminobis(phosphonite), PhN{P(−OC10H6(μ-S)C10H6O−)}2 (2), containing a mesocyclic thioether backbone is synthesized by either treating PhN(PCl2)2 with 2 equiv of thiobis(2,2‘-naphthol) or reacting chlorophosphite (−OC10H6(μ-S)C10H6O−)PCl (1) with aniline in the presence of a base. Treatment of 2 with an equimolar amount of Pd(COD)Cl2 in the presence of H2O affords a P−N−P-bridged and P,S-metalated binuclear complex, [PhN(P(−OC10H6(μ-S)C10H6O−)-κP)2Pd2Cl2{P(−OC10H6(μ-S)C10H6O−)(O)-κP,κS}2] (3), whereas the same reaction with 2 equiv of Pd(COD)Cl2 in the presence of H2O and Et3N produces the mononuclear anionic complex [{(−OC10H6(μ-S)C10H6O−)P(O)-κP,κS}PdCl2](Et3NH) (5). By contrast, reaction of 2 with 2 equiv of Pd(COD)Cl2 and H2O in the absence of Et3N gives the hydrogen phosphonate coordinated complex [{(−OC10H6(μ-S)C10H6O−)P(OH)}PdCl2] (4) which converts to the anionic complex in solution or in the presence of a base. Compound 2 on treatment with Pt(COD)X2 (X = Cl or I) afforded P-coordinated four-membered chelate complexes [PhN(P(−OC10H6(μ-S)C10H6O−)-κP)2PtX2] (6 X = Cl, 7 X = I). The crystal structures of compounds 2, 3, 5, and 7 are reported. Compound 3 is the first example of a crystallographically characterized binuclear palladium complex containing a bidentate bridging ligand and its hydrolyzed fragments forming metallacycles containing a palladium−phosphorus σ bond. All palladium complexes proved to be very good catalysts for the Suzuki−Miyaura and Mizoroki−Heck cross-coupling and amination reactions with excellent turnover numbers (TON up to 1.46 × 105 in the case of the Suzuki−Miyaura reaction).

Large bite bisphosphite, 2,6-C5H3N{CH2OP(-OC10H6) - Punji, Benudhar; Balakrishna, Maravanji S. (Journal of Organometallic Chemistry, 2007)
<div class="abstract svAbstract " data-etype="ab" style="border: 0px; font-size: 16px; margin: 0px; padding: 0px; vertical-align: baseline; font-family: Arial, Helvetica, 'Lucida Sans Unicode', 'Microsoft Sans Serif', 'Segoe UI Symbol', STIXGeneral, 'Cambria Math', 'Arial Unicode MS', sans-serif; color: rgb(46, 46, 46); line-height: 23.68px;"> Large bite bisphosphite ligand, 2,6-C5H3N{CH2OP(–OC10H6)(μ-S)(C10H6O–)}2 (2), is obtained by reacting chlorophosphite, {-OC10H6(μ-S)C10H6O-}PCl (1) with 2,6-pyridinedimethanol in presence of triethylamine.Treatment of 2 with aqueous solution of H2O2 or elemental sulfur resulted in the formation of bis(oxide) or bis(sulfide) derivatives, 2,6-C5H3N{CH2OP(E)(–OC10H6)(μ-S)(C10H6O–)}2 (3, E = O; 4, E = S) in quantitative yield.The 10-membered cationic chelate complex, [RuCl(η6-C10H14)η2-2,6-C5H3N{CH2OP(–OC10H6)(μ-S)(C10H6O–)}2-κP,κP]Cl (5) is produced in the reaction between [Ru(p-cymene)(μ-Cl)(Cl)]2 and bisphosphite 2, whereas the neutral chelate complex, cis-[Rh(CO)Cl{2,6-C5H3N{CH2OP(–OC10H6(μ-S)C10H6O–)}2}-κP,κP] (6) is isolated in the reaction of 2 with 0.5 equiv.of [Rh(CO)2Cl]2.Compound 2 on treatment with M(COD)Cl2 (M = Pd, Pt) produce the chelate complexes, [MCl2{η2-2,6-C5H3N{CH2OP(–OC10H6)(μ-S)(C10H6O–)}2}-κP,κP] (7, M = Pd;10, M = Pt).Similarly the reaction of bisphosphite 2 with Pd(COD)MeCl affords cis-[PdMe(Cl)η2-2,6-C5H3N{CH2OP(–OC10H6)(μ-S)(C10H6O–)}2-κP,κP] (8).Treatment of 2 with [Pd(η3- C3H5)Cl]2 in the presence of AgClO4 furnish the cationic complex, [Pd(η3-C3H5)η2-2,6-C5H3N{CH2OP(–OC10H6)(μ-S)(C10H6O–)}2-κP,κP]ClO4 (9). The binuclear complex, [Au2Cl2{2,6-C5H3N{CH2OP(–OC10H6)(μ-S)(C10H6O–)}2}-κP,κP] (11) is obtained in the reaction of compound 2 with two equiv. of AuCl(SMe2), where the ligand exhibits bridged bidentate mode of coordination. All the complexes are characterized by the 1H NMR, 31P NMR, elemental analysis and mass spectroscopy data. The cationic ruthenium complex 5 is proved to be an active catalyst for the hydrogenation of styrene and α-methyl styrene.

O-2-Naphthyl diphenylthiophosphinate - Mague, Joel T.; Punji, Benudhar; Ganesamoorthy, Chelladurai; Balakrishna, Maravanji S. (Acta Crystallographica Section E-Crystallographic Communications, 2007)
The molecule of the title compound, C10H7OP(S)(C6H5)2 or C22H17OPS, exhibits distorted tetrahedral geometry about the P atom. The P=S bond of 1.9355 (4) Å is shorter than that found in Ph3P=S [1.950 (3) Å] because the replacement of one carbon on phosphorus by oxygen increases the effective electronegativity of the P atom, thereby enhancing pπ–dπ back-donation from a lone-pair orbital of the S atom.

Thioether-functionalized ferrocenyl-bis(phosphonite), Fe(C5H4)P(−OC10H6(μ-S)C10H6O−)2: synthesis, coordination behavior, and application in suzuki-miyaura cross-coupling reactions - Punji, Benudhar; Mague, Joel T.; Balakrishna, Maravanji S. (Inorganic Chemistry, 2007)
The thioether-functionalized metalloligand ferrocenyl-bis(phosphonite), Fe(C5H4PR)2 (4, R = −OC10H6(μ-S)C10H6O−) is synthesized in three steps starting from ferrocene, and its coordination behavior toward various transition-metal derivatives is described. The reactions of 4 with [Rh(CO)2Cl]2 or M(COD)Cl2 afforded the chelate complexes, cis-[Rh(CO)Cl{Fe(C5H4PR)2-κP,κP}] (5) or cis-[MCl2{Fe(C5H4PR)2-κP,κP}] (6, M = PdII; 7, M = PtII), respectively. However, treatment of 4 with CuX (X = Cl, Br, and I) produces binuclear complexes, [Cu2(μ-X)2(MeCN){Fe(C5H4PR)2-κP,κP}] (8, X = Cl; 9, X = Br; 10, X = I) where the sulfur atom on one side of the ligand is involved in a weak interaction with the copper center. Reaction of 4 with 1 equiv of Ag(PPh3)OTf gives the mononuclear chelate complex [Ag(OTf)PPh3{Fe(C5H4PR)2-κP,κP}] (11), whereas treatment with 2 equiv of AuCl(SMe2) produces the dinuclear gold complex [Au(Cl){Fe(C5H4PR)2-κP,κP}Au(Cl)] (12). The crystal structures of 10 and 12 are reported, where a strong metallophilic interaction is observed between the closed-shell metal centers. The palladium complex 6 catalyzes the Suzuki cross-coupling reactions of aryl bromides with phenylboronic acid with excellent turnover numbers (TON up to 1.36 × 105).

Copper (I) complexes of a thioether-functionalized short-bite aminobis(phosphonite) - Punji, Benudhar; Mague, Joel T.; Mobin, Shaikh M.; Balakrishna, Maravanji S. (Polyhedron, 2009)
Copper(I) complexes of short-bite aminobis(phosphonite), PhN{P(–OC10H6(μ-S)C10H6O–)}2 (1) have been synthesized. Reactions of 1 with an excess of CuX (X = Cl, Br, and I) afforded the ligand-bridged binuclear complexes, [PhN(PR-κP)2{Cu(μ-X)(MeCN)}2] (2, X = Cl; 3, X = Br; 4, X = I; R = –OC10H6(μ-S)C10H6O–), whereas treatment with 0.5 equiv. of [Cu(MeCN)4]PF6 produces the mononuclear bischelated cationic complex, [{PhN(PR-κP)2}2Cu](PF6) (5). Single crystal X-ray structures of complexes 3 and 4 are reported. Complex 3 shows strong π–π stacking interactions between the naphthyl moieties, whereas complex 4 shows ligand-supported Cu⋯Cu metallophilic interactions.

Highly stable adamantyl-substituted pincer-ligated iridium catalyst for alkane dehydrogenation - Punji, Benudhar; Emge, Thomas J.; Goldman, Alan S. (Organometallics, 2010)
The adamantyl-substituted pincer-ligand precursor AdPCP-H [(AdPCP = κ3-C6H3-2,6-(CH2PAd2)2); Ad = 1-adamantyl] has been synthesized by the reaction of 1,3-dibromoxylene with di-1-adamantylphosphine in the presence of triethylamine. Treatment of AdPCP-H with [Ir(COD)Cl]2 (COD = 1,5-cyclooctadiene) affords the pincer-ligated complex (AdPCP)IrHCl, which was crystallographically characterized. Dehydrohalogenation of (AdPCP)IrHCl either with LiBEt3H or with KOtBu, under hydrogen atmosphere, yields the hydrides (AdPCP)IrH2 and (AdPCP)IrH4. (AdPCP)IrH2 catalyzes dehydrogenation of alkanes with a level of activity comparable to that of the previously reported (tBuPCP)IrH2, while it is thermally much more robust than the tBuPCP analogue, as well as iPrPCP or tBuPOCOP pincer complexes.

Large-bite bisphosphite, 1,3-C6H4OPOC10H6(μ-S)C10H6O2: synthesis, copper(I), and gold(I) complexes - Balakrishna, Maravanji S.; Kumar, Pawan; Punji, Benudhar; Mague, Joel T. (Journal of Organometallic Chemistry, 2010)
Large-bite bisphosphite ligand 1,3-C6H4{OPOC10H6(μ-S)C10H6O}2 (3), is obtained by reacting chlorophosphonite {OC10H6(μ-S)C10H6O}PCl (2) with resorcinol in the presence of triethylamine. Treatment of 3 with CuCl in 1:1 molar ratio produces a 1D-coordination polymer [CuCl{(–OC10H6(μ-S)C10H6O–)P(–OC6H4O–)P(–OC10H6(μ-S)C10H6O–)}-κP,κP]∞ (4) in good yield. Similar reaction of 3 with two equivalents of AuCl(SMe2) affords a dinuclear complex, [Au2Cl2{(–OC10H6(μ-S)C10H6O–)P(–OC6H4O–)P(–OC10H6(μ-S)C10H6O–)}-κP,κP] (5). Single crystal X-ray structures of the ligand 3 and the complexes 4 and 5 are reported. The gold complex 5 shows dimeric structure supported by strong Au···Au aurophilic interactions.

Catalytic dehydroaromatization of n-alkanes by pincer-ligated iridium complexes - Ahuja, Ritu; Punji, Benudhar; Findlater, Michael; Supplee, Carolyn; Schinski, William; Brookhart, Maurice; Goldman, Alan S. (Nature Chemistry, 2011)
Aromatic hydrocarbons are among the most important building blocks in the chemical industry. Benzene, toluene and xylenes are obtained from the high temperature thermolysis of alkanes. Higher alkylaromatics are generally derived from arene–olefin coupling, which gives branched products—that is, secondary alkyl arenes—with olefins higher than ethylene. The dehydrogenation of acyclic alkanes to give alkylaromatics can be achieved using heterogeneous catalysts at high temperatures, but with low yields and low selectivity. We present here the first catalytic conversion of n-alkanes to alkylaromatics using homogeneous or molecular catalysts—specifically ‘pincer’-ligated iridium complexes—and olefinic hydrogen acceptors. For example, the reaction of n-octane affords up to 86% yield of aromatic product, primarily o-xylene and secondarily ethylbenzene. In the case of n-decane and n-dodecane, the resulting alkylarenes are exclusively unbranched (that is, n-alkyl-substituted), with selectivity for the corresponding o-(n-alkyl)toluene.

User-friendly [(diglyme)NiBr2]-catalyzed direct alkylations of heteroarenes with unactivated alkyl halides through c?h bond cleavages - Ackermann, Lutz; Punji, Benudhar; Song, Weifeng (Advanced Synthesis & Catalysis, 2011)
A nitrogen and phosphorus ligand-free catalytic system derived from inexpensive [(diglyme)NiBr2] allowed for efficient direct C[BOND]H bond alkylations of heteroarenes with unactivated β-hydrogen-containing alkyl halides under basic reaction conditions.

Cobalt-catalyzed C–H bond functionalizations with aryl and alkyl chlorides - Punji, Benudhar; Song, Weifeng; Shevchenko, Grigory A.; Ackermann, Lutz (Chemistry - A European Journal, 2013)
Inexpensive cobalt catalysts derived from N-heterocylic carbenes (NHC) allowed efficient catalytic C[BOND]H bond arylations on heteroaryl-substituted arenes with widely available aryl chlorides, which set the stage for the preparation of sterically hindered tri-ortho-substituted biaryls. Likewise, challenging direct alkylations with β-hydrogen-containing primary and even secondary alkyl chlorides proceeded on pyridyl- and pyrimidyl-substituted arenes and heteroarenes. The cobalt-catalyzed C[BOND]H bond functionalizations occurred efficiently at ambient reaction temperature with excellent levels of site-selectivities and ample scope. Mechanistic studies highlighted that electron-deficient aryl chlorides reacted preferentially, while the arenes kinetic C[BOND]H bond acidity was found to largely govern their reactivity.

Rational design of highly active “hybrid” phosphine-phosphinite pincer iridium catalysts for alkane metathesis - Nawara-Hultzsch, Agnieszka J.; Hackenberg, Jason D.; Punji, Benudhar; Supplee, Carolyn; Emge, Thomas J.; Bailey, Brad C.; Schrock, Richard R.; Brookhart, Maurice; Goldman, Alan S. (ACS Catalysis, 2013)
Both the bisphosphine and bisphosphinite pincer complexes (tBu4PCP)IrH2 and (tBu4POCOP)IrH2 can cocatalyze alkane metathesis in tandem with olefin metathesis catalysts, but the two complexes have different resting states during catalysis, suggesting that different steps are turnover-limiting in each case. This led to the hypothesis that a complex with intermediate properties would be catalytically more active than either of these two species. Accordingly, “hybrid” phosphine–phosphinite pincer ligands (PCOP) and the corresponding iridium complexes were synthesized (3c–e). In tandem with olefin-metathesis catalyst MoF12, (tBu4PCOP)IrH2 displays significantly higher activity for the metathesis of n-hexane than does (tBu4PCP)IrH2 or (tBu4POCOP)IrH2. (tBu2PCOPiPr2)IrH4 (3d) is even more active (>30-fold more active than (tBu4POCOP)IrH2) and affords nearly 4.6 M alkane products after 8 h at 125 °C.

Recent advances in transition-metal-free direct C–C and C–heteroatom bond forming reactions - Mehta, Vaibhav P.; Punji, Benudhar (RSC Advances, 2013)
The efficient generation of biaryl compounds and heterocycles via the advent of the transition-metal-free coupling reaction constitutes an important development in the last few years. Although early methods for the construction of such molecules involved transition metals, recent advances in the field have witnessed a myriad of elegant reports without the use of metal sources. The serendipitous discovery and observation of synthetic chemists have realized that there lies a great potential in exploiting the inherent reactivity of molecules in absence of transition metal. The key to the success of such coupling reactions is the use of a strong base, oxidant and a catalytic amount of N-donor ligands which contribute significantly. This review aims to highlight the recent progress in the field of transition-metal-free direct C–C and C–heteroatom bond forming reactions via the use of a strong base and (or) an oxidant.

Design and development of POCN-pincer palladium catalysts for C-H bond arylation of azoles with aryl iodides - Khake, Shrikant M.; Soni, Vineeta; Gonnade, Rajesh G.; Punji, Benudhar (Dalton Transactions, 2014)
{Well-defined and efficient POCN-ligated palladium complexes have been developed for the direct C H bond arylation of azoles with aryl iodides. The phosphinite-amine pincer ligands 1-(R2PO)-C6H4-3-((CH2NPr2)-Pr-i) 1R2POCNIPr2-H; R = `Pr (1a)

Metal-free regioselective C-3 acetoxylation of N-substituted indoles: crucial impact of nitrogen-substituent - Soni, Vineeta; Patel, Ulhas N.; Punji, Benudhar (RSC Advances, 2015)
A metal-free method for the regioselective C-3 acetoxylation of the N-substituted indoles with PhI(OAc)(2) is described under mild reaction conditions. This method tolerates a broad range of functional groups with moderate to good yields. The pi-electron-deficient aryl-substituents on the N-atom of indoles and the acidic reaction medium remarkably favor C-3 acetoxylation.

Mono- and binuclear palladacycles via regioselective C-H bond activation: syntheses, mechanistic insights and catalytic activity in direct arylation of azoles - Pandey, Dilip K.; Khake, Shrikant M.; Gonnade, Rajesh G.; Punji, Benudhar (RSC Advances, 2015)
{Regioselective C-H bond palladation of the hybrid pincer-type ligands, 3-R2PO-C6H4-1-(CH2NPr2)-Pr-i [(POCNiPr2)-P-R2-H; R = Ph (1a)

Mechanistic insights into pincer-ligated palladium-catalyzed arylation of azoles with aryl Iodides: evidence of a Pd-II-Pd-IV-Pd-II pathway - Khake, Shrikant M.; Jagtap, Rahul A.; Dangat, Yuvraj B.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2016)
Pincer-based (R2POCNR′2)PdCl complexes along with CuI cocatalyst catalyze the arylation of azoles with aryl iodides to give the 2-arylated azole products. Herein, we report an extensive mechanistic investigation for the direct arylation of azoles involving a well-defined and highly efficient (iPr2POCNEt2)PdCl (2a) catalyst, which emphasizes a rare PdII–PdIV–PdII redox catalytic pathway. Kinetic studies and deuterium labeling experiments indicate that the C–H bond cleavage on azoles occurs via two distinct routes in a reversible manner. Controlled reactivity of the catalyst 2a underlines the iodo derivative (iPr2POCNEt2)PdI (3a) to be the resting state of the catalyst. The intermediate species (iPr2POCNEt2)Pd-benzothiazolyl (4a) has been isolated and structurally characterized. A determination of reaction rates of compound 4a with electronically different aryl iodides has revealed the kinetic significance of the oxidative addition of the C(sp2)–X electrophile, aryl iodide, to complex 4a. Furthermore, the reactivity behavior of 4a suggests that the arylation of benzothiazole proceeds via an oxidative addition/reductive elimination pathway involving a (iPr2POCNEt2)PdIV(benzothiazolyl)(Ar)I species, which is strongly supported by DFT calculations.

Synthesis of quinoline-based NNN-pincer nickel(II) complexes: a robust and improved catalyst system for C–H bond alkylation of azoles with alkyl halides - Patel, Ulhas N.; Pandey, Dilip K.; Gonnade, Rajesh G.; Punji, Benudhar (Organometallics, 2016)
The quinoline-based pincer nickel(II) complexes κN,κN,κN-{R2N-C6H4-(μ-N)-C9H6N}NiX ((R2NNNQ)NiCl: R = Me, 2a; R = Et, 2b) were synthesized by the reaction of the ligand precursors (R2NNNQ)H (R = Me, 1a; R = Et, 1b) with (DME)NiCl2 in the presence of Et3N. Similarly, the pincer nickel(II) derivatives (R2NNNQ)NiX (R = Me, X = Br, 3a; R = Et, X = Br, 3b; R = Me, X = OAc, 4a) were obtained by treatment of the ligands (R2NNNQ)H with the nickel precursor (THF)2NiBr2 or Ni(OAc)2. All of these complexes were characterized by 1H and 13C NMR spectroscopy as well as by elemental analysis. Further, the molecular structures of 2a and 3a,b were elucidated by X-ray crystallography. Complex 2a is found to be an efficient catalyst for the direct C–H bond alkylation of substituted benzothiazoles and oxazoles with various unactivated alkyl halides containing β-hydrogens under mild reaction conditions. The catalyst 2a is very robust and was recycled and reused five times for the alkylation reaction without a decrease in its catalytic activity. Preliminary studies reveal that the catalyst 2a acts as an active catalyst and the alkylation reaction appears to operate via a radical pathway.

Unified strategy for nickel-catalyzed C-2 Alkylation of indoles through chelation assistance - Soni, Vineeta; Jagtap, Rahul A.; Gonnade, Rajesh G.; Punji, Benudhar (ACS Catalysis, 2016)
A nickel-catalyzed direct C-2 alkylation of indoles through monodentate-chelation assistance has been described. This reaction proceeds via an unusual strategy by the use of a well-designed and defined (quinolinyl)amido–nickel catalyst, [{κN,κN,κN-Et2NCH2C(O)(μ-N)C9H6N}Ni(OAc)], providing a solution to the limitations associated with bidentate-chelate auxiliaries. The method allows coupling of indoles with various unactivated primary and secondary alkyl halides with ample substrate scope. This uniquely strategized alkylation proceeded through crucial C–H activation and via an alkyl radical intermediate. The reaction by this approach represents a rare example of Ni-catalyzed monodentate-chelate-assisted C–H functionalization.

Development of (quinolinyl)amido-based pincer palladium complexes: a robust and phosphine-free catalyst system for C–H arylation of benzothiazoles - Pandiri, Hanumanprasad; Soni, Vineeta; Gonnade, Rajesh G.; Punji, Benudhar (New Journal of Chemistry, 2017)
(Quinolinyl)amido-ligated palladium(II) complexes have been synthesized and applied in the catalytic C–H bond arylation of benzothiazoles. The tridentate ligand precursors R2N-C(O)CH2-(NH)-C9H6N [(R2NNN8-Q)–H; R2N = morpholinyl, Me-N-piperazinyl] and the pincer palladium complexes [κN,κN,κN-{R2N-C(O)CH2-(μ-N)-C9H6N}]PdX [(R2NNN8-Q)PdX {R2N = Et2N, morpholinyl, Me-N-piperazinyl; X = OAc or Cl}] were efficiently synthesized, and characterized by various analytical techniques. The iodo derivative (Et2NNN8-Q)PdI was obtained in excellent yield by the treatment of the complex (Et2NNN8-Q)PdCl with KI. The molecular structures of complexes (Et2NNN8-Q)Pd(OAc) (2a), (Et2NNN8-Q)PdCl (3a) and (Et2NNN8-Q)PdI (4a) were elucidated by X-ray crystallography. Complex 3a was found to be the most efficient catalyst for direct C–H bond arylation of substituted benzothiazoles with diverse aryl iodides using a mild base, K2CO3. The working catalyst system 3a is highly robust and can be recycled and reused several times for the arylation of benzothiazole without loss of catalytic activity. Preliminary mechanistic investigations using controlled studies and kinetic analysis have been performed, which greatly support a molecular mechanism for the arylation.

Expeditious and solvent-free nickel-catalyzed C−H arylation of arenes and indoles - Jagtap, Rahul A.; Soni, Vineeta; Punji, Benudhar (ChemSusChem, 2017)
An efficient solvent-free nickel-catalyzed method for C−H bond arylation of arenes and indoles has been developed, which proceeds expeditiously through chelation assistance. The reaction is highly selective for mono-arylation and tolerates sensitive and structurally diverse functionalities, such as halides, ethers, amines, indole, pyrrole and carbazole. This reaction represents the first example of a nickel-catalyzed C−H arylation by monochelate assistance and symbolizes a rare precedent in solvent-free C−H arylation. Mechanistic investigations by various controlled reactions, kinetic studies, and deuterium labeling experiments suggest that the arylation follows a single electron transfer (SET) pathway involving the turnover-limiting C−H nickelation process.

General nickel-catalyzed method for C-H bond alkynylation of heteroarenes through chelation assistance - Punji, Benudhar; Khake, Shrikant manmathappa; Soni, Vineeta; Gonnade, Rajesh Ghanshyam (Chemistry - A European Journal, 2017)
A general nickel-catalyzed method for the alkynylation of heteroarenes through monodentate chelation assistance is described. Many heterocycles, including indoles, pyrroles, imidazoles and pyrazole, efficiently coupled with (triisopropylsilyl)alkynyl bromide, and synthetically important functional groups, such as halides, ether, nitrile, nitro were tolerated. Synthetic applicability of this Ni-catalyzed method is demonstrated by the removal of triisopropylsilyl (-SiiPr₃) group, and further functionalization into triazolyl, benzofuranyl and alkynyl arene derivatives. Preliminary mechanistic investigations on the alkynylation of indole suggest that the reaction proceeds through kinetically relevant C-H activation and follows the two-electron redox pathway. A catalytically competent Ni-species, [(Phen)₃Ni].NiBr₄ has been isolated and structurally characterized.

Palladacycles for directed and nondirected C H bond functionalization of (Hetero)arenes - Soni, Vineeta; Punji, Benudhar (Strategies for palladium-catalyzed non-directed and directed C-H bond functionalization, 2017)
Application of palladacycle complexes in catalytic organic transformation is rapidly expanding. This chapter is mainly focused on the use of palladacycle precatalysts in CH bond functionalizations, as well as an overview of palladacycle intermediates in directed CH bond functionalization reactions. The described palladacycle precatalysts are more efficient and more selective than the traditional palladium complexes for CH bond functionalization processes. The second part of the chapter summarizes the involvement of palladacycle intermediates in various directed CH bond functionalizations that are proposed with experimental evidence. Some of the palladacycle intermediates described are shown to be competent as catalyst precursors. It has been demonstrated that the formation of palladacycle (precatalyst or intermediate) makes the CH functionalization process more facile, because of the high stability associated with palladacycles.

Copper- and phosphine-free nickel(II)-catalyzed method for C-H bond alkynylation of benzothiazoles and related azoles - Patel, Ulhas N.; Punji, Benudhar (Asian Journal of Organic Chemistry, 2018)
A phosphine-free nickel(II)-catalyzed method for the C(2)-H bond alkynylation of (benzo)thiazoles, (benz)imidazoles, and oxazoles is described. Well-defined and air-stable (Phen)NiCl2 catalyst efficiently catalyzes the coupling of diverse azoles with alkynyl bromides without the use of a copper co-catalyst, and the method tolerates synthetically important functional groups. Preliminary mechanistic studies on this Ni-II-catalyzed alkynylation emphasize the homogeneous nature of the catalyst, and rule out a radical manifold for the reaction. The synthetic utility of this Ni-catalyzed method is demonstrated by further functionalizing the alkynylated benzothiazoles to 3-methyl-2-(alkynyl)benzo[d]thiazolium salts that are known DNA cleaving agents.
Keywords: alkynylation; azoles; C-H activation; heterocycles; Nickel

Mechanism of nickel(II)-catalyzed C(2)-H alkynylation of indoles with alkynyl bromide - Khake, Shrikant M.; Jain, Shailja; Patel, Ulhas N.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2018)
The nickel system (THF)(2)NiBr2/phen has recently been shown as an efficient catalyst for the C-H bond alkynylation of diverse heteroarenes with (triisopropylsilyl)alkynyl bromide via monodentate chelation assistance. Herein, we report an extensive mechanistic investigation for the direct alkynylation of indoles involving the well-defined nickel catalyst, which features a coordinative insertion pathway of alkynyl bromide with the Ni(II) catalyst. Catalytic relevant nickel complexes, (phen)NiCl2 (5), (phen)(2)NiCl2 (6) and [(phen)(3)Ni].NiCl4 (7) were isolated, and the complexes 6 and 7 were structurally characterized. Well-defined complexes were as competent as the in situ generated catalyst system (THF)(2)NiBr2/phen for the alkynylation of indoles. Various controlled studies and reactivity experiments were performed to understand the probable pathway for the alkynylation reaction. Kinetics analysis highlights that the complex (phen)NiX2 acts as a precatalyst, and the involvement of substrate indole and LiO'Bu are essential for the generation of the active catalyst. Deuterium labeling and kinetic studies suggest that the process involving C-H cleavage and carbo-nickelation of indole is a crucial rate influencing step. Reactivity study of various alkynyl compounds with nickel-species highlights a migratory insertion route for the reaction. DFT calculations firmly support the experimental findings and suggest the coordinative insertion pathway of alkynyl bromide rather than oxidative addition toward the nickel(II) center.

Mechanistic aspects of pincer nickel(II)-catalyzed C-H bond alkylation of azoles with alkyl halides - Patel, Ulhas N.; Jain, Shailja; Pandey, Dilip K.; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Organometallics, 2018)
The quinolinyl-based pincer nickel complex, kappa(N),kappa(N),kappa(N)-{C9H6N-(mu-N)-C6H4-NMe2}NiCl [((NNNMe2)-N-Q)-NiCl; (1)] has recently been demonstrated to be an efficient and robust catalyst for the alkylation of azoles with alkyl halides under copper-free conditions. Herein, we report the detailed mechanistic investigation for the alkylation of azoles catalyzed by ((NNNMe2)-N-Q)NiCl (1), which highlights an iodine atom transfer (IAT) mechanism for the reaction involving a Ni-II/Ni-III process. Deuterium labeling experiments indicate reversible cleavage of the benzothiazole C-H bond, and kinetic studies underline a fractional negative rate order with the substrate benzothiazole. The involvement of an alkyl radical during the alkylation is validated by radical clock and external additive experiments. An active intermediate species ((NNNMe2)-N-Q)Ni(benzothiazolyl) (5a) has been isolated and structurally characterized. The complex ((NNNMe2)-N-Q)Ni(benzothiazoly1) (5a) is found to be the resting state of catalyst 1. Kinetic analysis of electronically different intermediates suggests that the step involving the reaction of 5a with alkyl iodide is crucial and a rate-influencing step. DFT calculations strongly support the experimental findings and corroborate an IAT process for the alkylation reaction.

Nickel-catalyzed regioselective C(2)-H difluoroalkylation of indoles with difluoroalkyl bromides - Soni, Vineeta; Sharma, Dipesh M.; Punji, Benudhar (Chemistry-An Asian Journal, 2018)
Regioselective C(2)-H difluoroalkylation of C-3 unsubstituted indoles with commonly available fluoroalkyl bromides is successfully achieved employing a simple nickel catalyst system, (DME)NiCl2/Xantphos. This methodology shows excellent regioselectivity and exhibits a broad substrate scope. Various functional groups, such as -OMe, -F, and -Br, are tolerated on the indole backbone to give the difluoroalkylated products in moderate to good yields. Preliminary mechanistic findings demonstrate that the reaction is homogeneous in nature and involves a radical manifold. Synthetic utility of this nickel-catalyzed method is demonstrated by synthesizing melatonin receptor antagonist Luzindole derivative.

Synthesis of quinolinyl based pincer copper (II) complexes: an efficient catalyst system for Kumada coupling of alkyl chlorides and bromides with alkyl Grignard reagents - Pandiri, Hanumanprasad; Gonnade, Rajesh G.; Punji, Benudhar (Dalton Transactions, 2018)
Quinolinamide-based pincer copper(ii) complexes, (N),(N),(N)-{C9H6N-(-N)-C(O)CH2NEt2}CuX [((NNN2Et)-N-Q)CuX (X = Cl, 2; X = Br, 3; X = OAc, 4)], were synthesized by the reaction of ligand ((NNN2Et)-N-Q)-H (1) with CuX2 (X = Cl, Br or OAc) in the presence of Et3N. The reaction of ((NNN2Et)-N-Q)-H with CuX (X = Cl, Br or OAc) also afforded the Cu(ii) complexes 2, 3 and 4, respectively, instead of the expected Cu(i) pincer complexes. The formation of Cu(ii) complexes from Cu(i) precursors most likely occurred via the disproportionation reaction of Cu(i) into Cu(0) and Cu(ii). A cationic complex [((NNN2Et)-N-Q)Cu(CH3CN)]OTf (5) was synthesized by the treatment of neutral complex 2 with AgOTf. On the other hand, the reaction of ((NNN2Et)-N-Q)-H (1) with [Cu(MeCN)(4)]ClO4 produced cationic Cu(i) complex, [((NN)-N-Q(H)N-2(Et))Cu(CH3CN)]ClO4 (6), in good yield. All complexes 2-5 were characterized by elemental analysis and HRMS measurements. Furthermore, the molecular structures of 2, 3 and 4 were elucidated by X-ray crystallography. Complex 4 crystallizes in a dimeric and catemeric pattern. The cationic complex 5 was found to be an efficient catalyst for the Kumada coupling reaction of diverse nonactivated alkyl chlorides and bromides with alkyl magnesium chloride under mild reaction conditions.

C-H functionalization of indoles by 3d transition-metal catalysis - Jagtap, Rahul A.; Punji, Benudhar (Asian Journal of Organic Chemistry, 2019)
Over the past decade, the use of 3d transition metal for the regioselective C-H bond functionalization of indoles has significantly increased. Particularly, advances in manganese, iron, cobalt, nickel and copper catalysis have demonstrated the selective C(2)-H and C(3)-H arylation, alkenylation, alkynylation and alkylation to a greater extent. Similarly, the C-O and C-N bond-forming reactions are manifested via direct C-H bond activation by these earth-abundant metals. The emergence of 3d metals in selective functionalization of the biologically relevant indoles and related heteroarenes would make this protocol more attractive for practical applications. Herein, we provide a brief overview of 3d transition metal-catalyzed (mostly Mn, Fe, Co, Ni and Cu) C-H functionalization of indoles and related heteroarenes.
Keywords: 3d transition metal; C-H functionalization; Indole; indoline

Nickel-catalyzed C(2)-H arylation of indoles with aryl chlorides under neat conditions - Pandey, Dilip K.; Vijaykumar, Muniyappa; Punji, Benudhar (Journal of Organic Chemistry, 2019)
Nickel-catalyzed regioselective C(2)-H arylation of indoles and pyrroles with aryl chlorides is achieved under neat conditions. This method allows the efficient coupling of diverse aryl chlorides employing a user-friendly and inexpensive Ni(OAc)(2)/dppf catalyst system at 80 degrees C. Numerous functionalities, such as halides, alkyl ether, fluoro-alkyl ether, and thioether, and substituted amines, including heteroarenes like benzothiazolyl, pyrrolyl, indolyl, and carbazolyl, are well tolerated under the reaction conditions. The preliminary mechanistic study highlights a single-electron transfer (SET) pathway for the arylation reaction.

Nickel-catalyzed C-H alkylation of indoles with unactivated alkyl chlorides: evidence of a Ni(i)/Ni(iii) pathway - Pandey, Dilip K.; Ankade, Shidheshwar B.; Ali, Abad; Vinod, C. P.; Punji, Benudhar (Chemical Science, 2019)
A mild and efficient nickel-catalyzed method for the coupling of unactivated primary and secondary alkyl chlorides with the C-H bond of indoles and pyrroles is described which demonstrates a high level of chemo and regioselectivity. The reaction tolerates numerous functionalities, such as halide, alkenyl, alkynyl, ether, thioether, furanyl, pyrrolyl, indolyl and carbazolyl groups including acyclic and cyclic alkyls under the reaction conditions. Mechanistic investigation highlights that the alkylation proceeds through a single-electron transfer (SET) process with Ni(i)-species being the active catalyst. Overall, the alkylation follows a Ni(i)/Ni(iii) pathway involving the rate-influencing two-step single-electron oxidative addition of alkyl chlorides.

Nickel-catalyzed straightforward and regioselective C-H alkenylation of indoles with alkenyl bromides: scope and mechanistic aspect - Jagtap, Rahul A.; Vinod, C. P.; Punji, Benudhar (ACS Catalysis, 2019)
Nickel-catalyzed regioselective C-H bond alkenylation of indoles and related heteroarenes with alkenyl bromides is accomplished under relatively mild conditions. This method allows the straightforward synthesis of C-2 alkenylated indoles employing an air-stable and well-defined nickel catalyst, (bpy)NiBr2, providing a solution to the limitations associated with hydroindolation and oxidative alkenylation. The reaction conceded the coupling of indole derivatives with various alkenyl bromides, such as aromatic and heteroaromatics, alpha- and beta-substituted as well as exo- and endo-cyclic alkenyl compounds. An extensive mechanistic investigation, including controlled study, reactivity experiments, kinetics and labeling studies, and EPR and XPS analyses, highlights that the alkenylation proceeds through a single-electron transfer process comprising an odd-electron oxidative addition of alkenyl bromide. Furthermore, the alkenylation operates via a probable Ni(I)/Ni(III) pathway involving the rate-limiting C-H nickelation of indole.
Keywords: alkenylation; C-H activation; indoles; Mechanism; Nickel; single-electron transfer

Scope and mechanistic aspect of nickel-catalyzed alkenylation of benzothiazoles and related azoles with styryl bromides - Patel, Ulhas N.; Jagtap, Rahul A.; Punji, Benudhar (Organometallics, 2019)
Alkenylation of benzothiazoles and related azoles with alkenyl bromides is achieved employing the well-defined and air-stable nickel complexes, (bpy)NiBr2 and [Ni(bpy)(3)] [NiBr4], as catalysts. Numerous electronically distinct alkenyl bromides efficiently coupled with substituted benzothiazoles, oxazoles, and benzimidazoles under the catalytic conditions to afford 2-alkenylated azoles. An extensive mechanistic study of the alkenylation of benzothiazole using (bpy)NiBr2 highlights a single-electron transfer process for the reaction involving the two-step one-electron oxidative addition of alkenyl bromide. The substrate benzothiazole plays a significant and diverse role in the reaction, and C-H bond cleavage is reversible in nature. Detailed kinetic analysis and control reactivity studies are indicative of a Ni(I)/Ni(III) pathway for the alkenylation comprising the rate-influencing reductive elimination step.

Selective synthesis of secondary amines from nitriles by a user-friendly cobalt catalyst - Sharma, Dipesh M.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2019)
Selective hydrogenation/reductive amination of nitriles to secondary amines catalyzed by an inexpensive and user-friendly cobalt complex, (Xantphos)CoCl2, is reported. The use of (Xantphos)CoCl2 and ammonia borane (NH3-BH3) combination affords the selective reduction of nitriles to symmetrical secondary amines, whereas the employment of (Xantphos)CoCl2 and dimethylamine borane (Me2NH-BH3) along with external amines produce unsymmetrical secondary amines and tertiary amines. The general applicability of this methodology is demonstrated by the synthesis of 43 symmetrical and unsymmetrical secondary and tertiary amines bearing diverse functionalities.

3 d transition metal-catalyzed hydrogenation of nitriles and alkynes - Sharma, Dipesh M.; Punji, Benudhar (Chemistry-An Asian Journal, 2020)
Selective hydrogenation of nitriles and alkynes is crucial considering the vast applications of reduced products in industries and in the synthesis of bioactive compounds. Particularly, the late 3d transition metal catalysts (manganese, iron, cobalt, nickel and copper) have shown promising activity for the hydrogenation of nitriles to primary amines, secondary amines and imines. Similarly, semihydrogenation of alkynes to E- and Z-alkenes by 3d metals is adequately successful both via the transfer hydrogenation and by using molecular hydrogen. The emergence of 3d transition metals in the selective synthesis of industrially relevant amines, imines and alkenes makes this protocol more attractive. Herein, we provide a concise overview on the late 3d transition metal-catalyzed hydrogenation of nitriles to amines and imines as well as semihydrogenation of alkynes to alkenes.
Keywords: 3d transition metal; Alkynes; Hydrogenation; nitriles; Semihydrogenation

Copper-catalyzed direct arylation of indoles and related (hetero)arenes: a ligandless and solvent-free approach - Pandey, Dilip K.; Shabade, Anand B.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2020)
A ligandless and solvent-free copper-catalyzed method for the regioselective C-H bond arylation of indoles and related heteroarenes is reported. The use of CuCl efficiently catalyzes the direct coupling of diverse heteroarenes with aryl iodides via chelation-assistance. This reaction could tolerate sensitive and structurally diverse functionalities, including halides, ethers, thioethers, amines, indolyl, pyrrolyl and carbazolyl groups. The directing group, 2-pyridinyl can be smoothly removed to generate C-2 arylated free-NH indoles, and the arylated indoles can further be functionalized into Tryptamine derivatives. Preliminary mechanistic study revealed a radical pathway for the arylation reaction.
Keywords: Arylation; C-H activation; Chelation-assistance; Copper; Indole; Solvent-free

Expeditious and solvent-free nickel-catalyzed c-h arylation of arenes and indoles (vol 10, pg 2242, 2017) - Jagtap, Rahul A.; Soni, Vineeta; Punji, Benudhar (ChemSusChem, 2020)
Keywords: Arylation; C-H activation; heterocycles; Homogeneous catalysis; Nickel

Iron-catalyzed C(sp(2))-H alkylation of indolines and benzo[h]quinoline with unactivated alkyl chlorides through chelation assistance - Jagtap, Rahul A.; Samal, Pragnya Paramita; Vinod, C. P.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2020)
Regioselective C-H bond alkylation of indolines and benzo[h]quinoline with a wide range of unactivated and highly demanded primary and secondary alkyl chlorides is accomplished using a low-cost iron catalyst. This reaction tolerates diverse functionalities, such as C(sp(2))-Cl, fluoro, alkenyl, silyl, ether, thioether, pyrrolyl, and carbazolyl groups including cyclic and acyclic alkyls as well as alkyl-bearing fatty-alcohol and polycyclic-steroid moieties. The demonstrated iron-catalyzed protocol proceeded via either a five-membered or a six-membered metallacycle. Intriguingly, the C-7-alkylated indolines can be readily functionalized into free-NH indolines/indoles and tryptamine derivatives. A detailed mechanistic investigation highlights the participation of an active Fe(I) catalyst and the involvement of a halogen-atom transfer process via a single-electron-based mechanism. Deuterium labeling and kinetics analysis indicate that the C-H metalation of indoline is the probable turnover-limiting step. Overall, the experimental and theoretical studies supported an Fe(I)/Fe(III) pathway for the alkylation reaction comprising the two-step, one-electron oxidative addition of alkyl chloride.
Keywords: alkyl chlorides; Alkylation; C-H activation; chelation assistance; indolines; iron

MnBr2-catalyzed direct and site-selective alkylation of indoles and benzo[h]quinoline - Jagtap, Rahul A.; Verma, Suryadev K.; Punji, Benudhar (Organic Letters, 2020)
Manganese-catalyzed regioselective C-H alkylation of indoles and benzo[h]quinoline with a variety of unactivated alkyl iodides is reported. Unlike other Mn-catalyzed C-H functionalization, this protocol does not require a Grignard reagent base and employs a simple and inexpensive MnBr2 as a catalyst. This method tolerates diverse functionalities, including fluoro, chloro, bromo, iodo, alkenyl, alkynyl, pyrrolyl, and carbazolyl groups. The alkylation proceeds through a single-electron transfer pathway comprising reversible C-H manganesation and involving an alkyl radical intermediate.

Achiral and chiral NNN-pincer nickel complexes with oxazolinyl backbones: application in transfer hydrogenation of ketones - Jagtap, Rahul A.; Ankade, Shidheshwar B.; Gonnade, Rajesh G.; Punji, Benudhar (New Journal of Chemistry, 2021)
We describe the synthesis of new NNN-oxazolinyl-pincer nickel complexes and their application in the transfer hydrogenation of ketones. Achiral NNN-ligands, R `(2)-oxazolinyl-2-C6H4-NH-C(O)CH2NEt2 [((R ` 2-OxNNNEt2))-H; R' = H (3a), R ` = Me (3b)], and chiral ligands, (R)-R `-oxazolinyl-2-C6H4-NH-C(O)CH2NEt2 [(R)-((R `-OxNNNEt2))-H; R ` = Ph (3c), R ` = CH2Ph (3d), R ` = Pr-i (3e), R ` = (CH2Pr)-Pr-i (3f)], were efficiently synthesized. Treatment of these ligands with (DME)NiCl2 afforded the desired amido-pincer nickel complexes, ((R ` 2-OxNNNEt2))NiCl [R ` = H (4a), R ` = Me (4b)] and ((R `-OxNNNEt2))NiCl [R ` = Ph (4c), R ` = CH2Ph (4d), R ` = Pr-i (4e), R ` = (CH2Pr)-Pr-i (4f)], in good yields. All the ligand precursors and nickel complexes were thoroughly characterized by various analytical techniques. The molecular structures of 4a, 4d and 4f were established by X-ray crystallography. The developed nickel complexes were found to be efficient catalysts for the transfer hydrogenation of ketones using (PrOH)-Pr-i as a viable hydrogen source. Enantioselectivity in hydrogenation was not observed with the developed chiral catalysts.

Advances in C(sp(2))-H/C(sp(2))-H oxidative coupling of (Hetero)arenes using 3d transition metal catalysts - Bansal, Sadhna; Shabade, Anand B.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2021)
C-H/C-H oxidative coupling has emerged as a straightforward and powerful technique for the construction of (hetero)biaryls, with substantial application to drug discovery, agrochemicals, biology, and material sciences. Mainly aryl-aryl, aryl-heteroaryl, and heteroaryl-heteroaryl couplings via double C(sp(2))-H activation using 4d or 5d noble transition metal catalysts have been extensively studied. Considering the earth-abundant and inexpensive nature of 3d transition metals, the sustainable development of C(sp(2))-H/C(sp(2))-H oxidative coupling employing such metal catalysts has gained significant attention. In this review, we present a comprehensive overview of C(sp(2))-H/C(sp(2))-H oxidative coupling of (hetero)arenes catalyzed by 3d transition metals.
Keywords: (hetero)biaryls; 3d transition metal; Biaryls; C-H activation; cross-dehydrogenative coupling

Advances in transition-metal-catalyzed C-H bond oxygenation of amides - Vijaykumar, Muniyappa; Punji, Benudhar (Synthesis-Stuttgart, 2021)
C-O bond formation represents a fundamental chemical transformation in organic synthesis to develop valuably oxygenated (hetero)arenes. Particularly, the direct and regioselective C-H bond oxygenation of privileged amides, using a transition metal catalyst and a mild oxygenating source, is a step-economy and attractive approach. During the last decade, considerable progress has been realized in the direct C-H oxygenation of primary, secondary, and tertiary amides. This Short Review compiles the advances in transition-metal-catalyzed oxygenation of C(sp(2))-H and C(sp(3))-H bonds on various amides with diverse oxygenation sources. The review is categorized into two different major sections: (i) C(sp(2))-H oxygenation and (ii) C(sp(3))-H oxygenation. Each section is discussed based on the directing group (monodentate and bidentate) attached to the amide derivatives.
Keywords: Amides; C-H activation; directing group; Oxygenation; Transition Metal

Nickel-catalyzed C-H bond functionalization of azoles and indoles - Jagtap, Rahul A.; Punji, Benudhar (Chemical Record, 2021)
Direct C-H functionalization of privileged and biologically relevant azoles and indoles represents an important chemical transformation in molecular science. Despite significant progress in the palladium-catalyzed regioselective C-H functionalization of azoles and indoles, the use of abundant and less expensive nickel catalyst is underdeveloped. In the recent past, the nickel-catalyzed regioselective C-H alkylation, arylation, alkenylation and alkynylation of azoles and indoles have been substantially explored, which can be applied to the complex organic molecule synthesis. In this Account, we summarize the developments in nickel-catalyzed regioselective functionalization of azoles and indoles with a considerable focus on the reaction mechanism.
Keywords: azoles; C-C Bond formation; C-H functionalization; indoles; Nickel

Ni(II)-catalyzed intramolecular C-H/C-H oxidative coupling: an efficient route to functionalized cycloindolones and indenoindolones - Ankade, Shidheshwar B.; Samal, Pragnya Paramita; Soni, Vineeta; Gonnade, Rajesh G.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2021)
Nickel(II)-catalyzed intramolecular C(sp(2))-H/C(sp(3))-H and C(sp(2))-H/C(sp(2))-H oxidative couplings in indoles are achieved via chelation assistance. These reactions provide access to biologically relevant five- and six-membered substituted cyclopentaindolones, carbazolones, and indenoindolones in high yields and good chemoselectivity employing an air-stable and defined nickel catalyst, (bpy)Ni(OAc)(2). The oxidative cyclizations proceeded either through a six-membered or an unconventional seven-membered nickelacycle. An extensive mechanistic investigation by experiments and theoretical calculations revealed a facile indole's C(2)-H nickelation and a rate-limiting reductive elimination process. This intramolecular oxidative cyclization operates via a probable Ni(II)/Ni(III) pathway involving single-electron oxidation of nickel without the participation of a carbon-based radical.
Keywords: C-H activation; cycloindolones; indenoindolones; indoles; Mechanism; Nickel; oxidative coupling

Pd(II)-catalyzed chemoselective acetoxylation of C(sp(2))-H and C(sp(3))-H bonds in tertiary amides - Vijaykumar, Muniyappa; Punji, Benudhar (Journal of Organic Chemistry, 2021)
Palladium-catalyzed chemoselective C(sp(2))-H and C(sp(3))-H acetoxylation of synthetically useful tertiary amides is reported under relatively mild reaction conditions. This protocol proceeds through the assistance of a weakly coordinated directing group (C = O) and requires low catalyst (1.0 mol %) loading. Diverse functionalities, such as C(sp(2))-Cl, C(sp(3))-Cl, -CF3, -COOEt, and -NO2 groups, including morpholinyl, piperazinyl, and pyrrolidinyl heterocycles, are compatible under the reaction conditions. Further functionalization of this protocol is demonstrated by hydrolysis to alcohols, alcohol-acids, as well as reduction to tertiary amines. A preliminary kinetic isotope effect study supported the rate-limiting C-H bond activation process.

Unactivated alkyl halides in transition-metal-catalyzed C-H bond alkylation - Ankade, Shidheshwar B.; Shabade, Anand B.; Soni, Vineeta; Punji, Benudhar (ACS Catalysis, 2021)
Alkylation represents an important organic transformation in molecular science to develop privileged alkylated arenes and heteroarenes. Especially, the direct C-H bond alkylation using unactivated alkyl halides is a straightforward and attractive approach from both the step-economy and chemoselectivity perspectives. Substantial progress has been made in the direct alkylation using primary, secondary, and tertiary alkyl halides along with the methylation and fluoroalkylation. This Review broadly summarizes the transition-metal-catalyzed alkylations of C-H bonds on various arenes and heteroarenes with unactivated alkyl halides until October 2020. On the basis of the substrates utilized for alkylation, the Review is divided into two major sections: alkylation of arenes and alkylation of heteroarenes.
Keywords: (hetero)arenes; Alkylation; C-H activation; transition metals; unactivated alkyl halides

Efficient route to 3,3 `-biindolinylidene-diones by iron-catalyzed dimerization of isatins - Jagtap, Rahul A.; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Chemistry-an Asian Journal, 2022)
Iron-catalyzed dimerization of various isatin derivatives is described for the efficient synthesis of 3,3 `-biindolinylidene-diones (isoindigos). The reaction provides easy access to self-coupled and cross-coupled 3,3 `-indolinylidene-diones that have high relevance to biology and materials. This Fe(0)- or Fe(II)-catalyzed dimerization reaction tolerates a wide range of functionalities, such as fluoro, chloro, bromo, alkenyl, nitrile, ether, ester, pyrrolyl, indolyl and carbazolyl groups, including cyclic and acyclic alkyls as well as an alkyl-bearing fatty-alcohol moiety. Especially, the coupling between two distinct isatins provided excellent selectivity for the cross-dimerization with trace of self-couplings. The single-crystal X-ray diffraction study established the molecular structure of eight dimerized products. A preliminary mechanistic study of the Fe-catalyzed dimerization supported the radical pathway for the reaction.
Keywords: Cross-coupling; dimerization; iron; Isatin; Isoindigo; Mechanism

Manganese-catalyzed C(sp(2))-H alkylation of indolines and arenes with unactivated alkyl bromides - Verma, Suryadev K.; Punji, Benudhar (Chemistry-an Asian Journal, 2022)
Selective C(sp(2))-H bond alkylation of indoline, carbazole and (2-pyridinyl)arenes with unactivated alkyl bromides is achieved using MnBr2 catalyst in the absence of an external ligand. The alkylation uses a simple LiHMDS base and avoids the necessity of Grignard reagent, unlike other Mn-catalyzed C-H functionalization. This reaction proceeded either through a five- or a less-favored six-membered metallacycle, and tolerated diverse functionalities, including alkenyl, alkynyl, silyl, aryl ether, pyrrolyl, indolyl, carbazolyl and alkyl bearing fatty alcohol and polycyclic-steroid moieties. Alkylation follows a single electron transfer (SET) pathway involving 1e oxidative addition of alkyl bromide and a rate-limiting C-H metalation.
Keywords: Alkylation; C-H activation; indoline; ligand-free; manganese

Room temperature chemoselective hydrogenation of C=C, C=O and C=N bonds by using a well-defined mixed donor Mn(I) pincer catalyst - Shabade, Anand B.; Sharma, Dipesh M.; Bajpai, Priyam; Gonnade, Rajesh G.; Vanka, Kumar; Punji, Benudhar (Chemical Science, 2022)
Chemoselective hydrogenation of C=C, C=O and C=N bonds in alpha,beta-unsaturated ketones, aldehydes and imines is accomplished at room temperature (27 degrees C) using a well-defined Mn(I) catalyst and 5.0 bar H-2. Amongst the three mixed-donor Mn(I) complexes developed, kappa(3)-((PNNPyz)-P-R2-N-3)Mn(CO)(2)Br (R = Ph, Pr-i, Bu-t); the Bu-t -substituted complex ((PNNPyz)-P-tBu2-N-3)Mn(CO)(2)Br shows exceptional chemoselective catalytic reduction of unsaturated bonds. This hydrogenation protocol tolerates a range of highly susceptible functionalities, such as halides (-F, -Cl, -Br, and -I), alkoxy and hydroxy, including hydrogen-sensitive moieties like acetyl, nitrile, nitro, epoxide, and unconjugated alkenyl and alkynyl groups. Additionally, the disclosed method applies to indole, pyrrole, furan, thiophene, and pyridine-containing unsaturated ketones leading to the corresponding saturated ketones. The C=C bond is chemoselectively hydrogenated in alpha,beta-unsaturated ketones, while the aldehyde's C=O bond and imine's C=N bond are preferentially reduced over the C=C bond. A detailed mechanistic study highlighted the non-innocent behavior of the ligand in the ((PNNPyz)-P-tBu2-N-3) Mn(I) complex and indicated a metal-ligand cooperative catalytic pathway. The molecular hydrogen (H-2) acts as a hydride source, whereas MeOH provides a proton for hydrogenation. DFT energy calculations supported the facile progress of most catalytic steps, involving a crucial turnover-limiting H-2 activation.

Room temperature Z-selective hydrogenation of alkynes by hemilabile and non-innocent (NNN)Co(ii) catalysts - Sharma, Dipesh M.; Gouda, Chandrakant; Gonnade, Rajesh G.; Punji, Benudhar (Catalysis Science & Technology, 2022)
Hemilabile and phosphine-free quinolinyl-based NNN-type pincer and non-pincer cobalt complexes were developed for the room temperature catalytic transfer semi-hydrogenation of alkynes to Z-alkenes. Treatment of the quinolinyl-amine ligand, [C9H6N(NH)CH2CH2NEt2] ((NNN2NEt2)-N-Q-N-CH)-H with CoX2 afforded the pincer complexes kappa(3)-((NNN2NEt2)-N-Q-N-CH)CoX2 (X = Cl, Br), whereas, the quinolinyl-amide ligand, [C9H6N(NH)C(O)CH2NEt2] ((NNNNEt2)-N-Q-N-C(O))-H gave chelate anionic complexes kappa(2)-((NN)-N-Q)CoX2((NHNEt2)-H-C(O)) (X = Cl, Br). The well-defined anionic non-pincer cobalt complexes efficiently catalyzed the semi-hydrogenation of diverse alkynes to deliver highly chemoselective and stereodivergent Z-alkenes at room temperature. This hydrogenation exhibited broad substrate scope with the tolerance of sensitive functional groups, such as -Cl, -Br, -I, -OH, -NH2, -COOMe, and pyridinyl, employing a stable and user-friendly ammonia borane hydrogen source.

Advances in the iron-catalyzed direct functionalizations of heterocycles - Pradhan, Chandini; Punji, Benudhar (Synlett, 2023)
Direct functionalization of heterocycles is an advanced strategy for diversifying privileged and biorelevant heterocycle-containing molecules. Particularly, use of the most abundant transition metal, iron, as a catalyst makes this process highly cost-effective and sustainable. Recently, some progress has been realized towards the direct functionalization of heterocycles under iron catalysis. Herein, we present the developments in the C-H bond functionalizations and related reactions of various heterocycles by abundant iron salts. This Synpacts is categorized into different sections based on heterocycles being functionalized, and each section is discussed based on the type of reaction catalyzed by iron. 1 Introduction 2 Functionalization of Indoles 2.1 Alkylation 2.2 Alkenylation 2.3 Other Reactions 3 Oxindoles and isatins 3.1 C-C Bond Formation 3.2 C-Heteroatom Bond Formation 4 Pyridines and Furans 5 Functionalization of Azoles 6 Summary and Outlook
Keywords: Alkylation; azoles; C-H functionalization; heterocycles; indoles; iron; Mechanism

Chemodivergent coupling of azoarenes with benzyl alcohols via a borrowing hydrogen strategy using a well-defined nickel catalyst - Bansal, Sadhna; Gonnade, Rajesh G.; Punji, Benudhar (Catalysis Science & Technology, 2023)
Chemodivergent (de)hydrogenative coupling of azoarenes with benzyl alcohols is achieved via the N=N bond activation using an inexpensive and well-defined (6-OH-bpy)NiCl2 catalyst. This protocol highlights the construction of C-N bonds via a borrowing hydrogen strategy that offers substituted imines and amines. A range of azo compounds couple with various substituted benzyl alcohols in a tandem hydrogenation/dehydrogenation process. The nickel catalyst along with the K2CO3 or (KOBu)-Bu-t base governed the selectivity in imine and amine formation. A preliminary mechanistic study establishes the crucial role of metal-ligand cooperation (MLC) comprising the distinct radical pathways.

Iron-catalyzed regioselective C-H alkylation of indoles: an additive-free approach in renewable solvent - Pradhan, Chandini; Jagtap, Rahul A.; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Punji, Benudhar (Green Chemistry, 2023)
Alkylated indoles are important motifs in various biologically active molecules and drug candidates. Herein, we report a mild and efficient iron-catalyzed protocol for synthesizing alkylated indoles via C-H bond alkylation of indoles with unactivated alkenes, demonstrating a high level of regioselectivity. The reaction occurs under additive-free, solvent-free (or trace green solvent, 2-MeTHF) and less energy-intensive conditions using a sustainable metal catalyst and provides easy access to privileged alkylated indoles with anti-Markovnikov selectivity. Alkylation is compatible with important functionalities, such as fluoro, chloro, trifluoromethyl, alkenyl, ether, thioether, silyl, and siloxane, including heteroaryl, pyridinyl, carbazolyl, and indolyl moieties (45 examples, up to 96% yield). The developed protocol is very simple, straightforward, and fully accords with the principles of green chemistry. A detailed mechanistic investigation manifests the facile indole's C-H activation at the Fe(0) center, reversible 1,2-insertion of the alkene into the Fe-H bond of a metallacycle, and a turnover-limiting reductive elimination. Alkylated indoles are important motifs in various biologically active molecules and drug candidates.
Keywords: Aromatic Ketones; Green; organic synthesis

Palladium-catalyzed chemoselective oxygenation of C(sp2)-H and C(sp3)-H bonds in isatins - Vijaykumar, Muniyappa; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Organic Letters, 2023)
The palladium-catalyzed chemoselective C(sp2)-H and C(sp3)-H bond oxygenation of substituted isatin derivatives is reported. This mild protocol exhibits the C5 C(sp2)-H oxygenation of isatins through electrophilic intermolecular C-H palladation in concentrated solutions using PhI(OAc)2 or Selectfluor as an oxidant, whereas it exhibits- N-CH3 C(sp3)-H oxygenation in dilute solutions via carbonyl-assisted intramolecular palladation in the presence of K2S2O8. This oxygenation reaction provides a direct and unified approach for synthesizing diverse oxygenated isatins with sensitive functionalities, including biorelevant compounds.

Advancement in the C-H bond alkylation of (hetero)arenes catalyzed by the most abundant transition metal-iron - Pradhan, Chandini; Punji, Benudhar (Organic Chemistry Frontiers, 2024)
Alkylation reaction stands as a crucial organic transformation, fostering privileged alkylated arenes and heteroarenes in molecular science. Over the past decade, the utilization of the most abundant transition metal iron for regioselective C-H bond alkylation has gained substantial prominence, offering a straightforward and sustainable approach. Noteworthy progress has been achieved in the alkylation of diverse arenes and heteroarenes involving primary, secondary, and tertiary alkyl (pseudo)halide, alkene, and alcohol coupling partners via both the mono- and bidentate-chelate strategies. This concise and focused review provides an overview of the advancement in the iron-catalyzed alkylation of arenes and heteroarenes through step-economical C-H functionalization, their novel features, proposed mechanisms, and future research directions. The review is categorized into two major sections: (i) alkylation of arenes and (ii) alkylation of heteroarenes. Each section is discussed based on the class of arenes and heteroarenes used. Advancement in the direct C-H bond alkylation of arenes and heteroarenes using the catalysts based on the most abundant transition metal, iron, is summarized.

Chelation-assisted and steric-controlled selectivity in the Pd-catalyzed C-H/C-H oxidative coupling of indoles - Vijaykumar, Muniyappa; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Chemical Communications, 2024)
We report the first regioselective C2-C7 oxidative coupling of indoles using a palladium catalyst upon the strategic installation of N-pyridinyl and C3-carbonyl, which delivers 2,7-biindoles with a broad scope (25 examples; up to 93% yield). Isolation of the catalytic intermediate reveals the initial activation of the C(7)-H bond, followed by the C(2)-H bond in indoles, and the reaction proceeds via a Pd(ii)/Pd(0) pathway. This manuscript describes the first regioselective C2-C7 oxidative coupling of indoles using a palladium catalyst through the strategic installation of N-pyridinyl and C3-carbonyl, which delivers diverse biorelevant 2-7-biindoles.

Chemodivergent dehydrogenative coupling of alcohols by 3d metal catalysts - Bansal, Sadhna; Punji, Benudhar (ChemCatChem, 2024)
Chemodivergent synthesis by transition metal catalysts is a straightforward and sustainable approach to achieving valuable organic compounds. Especially, the chemodivergent dehydrogenative couplings of alcohols with organic motifs to develop various saturated and unsaturated compounds are highly environmentally benign due to the reduced waste generation. In this concept review, we presented the 3d transition metal (Mn, Fe, Co, and Ni)-catalyzed chemodivergent synthesis of imines and amines, saturated and unsaturated carbonyl/alcohol compounds, saturated and unsaturated nitriles, N-heterocycles, and N-/C-alkylated indoles. The discussed reaction commanded two or three different products with high chemoselectivity by changing specific reaction parameters, but keeping the catalyst unchanged. Generally, the acceptorless dehydrogenative coupling (ADC) provides unsaturated moieties, whereas the borrowing-hydrogen (BH) process results in saturated compounds. Text for Table of Contents: An overview of the chemodivergent dehydrogenative coupling of alcohols by the Earth-abundant transition metal catalysts is discussed. image
Keywords: 3d metals; Alcohols; chemodivergent; dehydrogenative coupling; heterocycles

Copper-catalyzed regioselective C-H alkylation of phenol derivatives with unactivated alkyl chlorides: manifesting a Cu(I)/Cu(III) pathway - Verma, Suryadev K.; Punji, Benudhar (Journal of Catalysis, 2024)
The use of unactivated alkyl chlorides in regioselective C -H alkylation is a highly challenging process with diverse applications of alkylation strategy in drug discovery and agrochemistry. In this work, we report an efficient and cost-effective copper -catalyzed protocol for the coupling of unactivated alkyl chlorides with the C -H bond of phenol derivatives via 2-pyridinyl chelation assistance. The reaction shows a high level of regioselectivity, leading to an exclusive ortho alkylation and providing a broad scope with the endurance of numerous functionalities such as silyl, ether, thioether, pyrrolyl, indolyl, carbazolyl groups, including alkyl bearing fatty alcohol, nonylphenol, and vitamin E. Detailed mechanistic investigations suggest that the alkylation occurs through a two -electron oxidative addition of alkyl chloride to an active Cu(I) species. Deuterium labeling and kinetics experiments indicate a facile and reversible C -H bond activation process. Overall, the alkylation follows a Cu(I)/Cu(III) pathway involving chelation-assisted smooth C -H metalation and rate -limiting C-Cl oxidative addition of alkyl chloride.

Iron-catalyzed C-C and C-N bond-forming tandem amidation offering access to 3-amino-3-aminomethyl-2-oxindole frameworks - Ankade, Shidheshwar B.; Pradhan, Chandini; Samal, Pragnya Paramita; Gonnade, Rajesh G.; Krishnamurty, Sailaja; Punji, Benudhar (Advanced Synthesis & Catalysis, 2024)
An iron-catalyzed protocol for the synthesis of 3-amino-3-aminomethyl-2-oxindole heterocyclic structures is disclosed employing isatins and non-nucleophilic N-methoxybenzamides. This reaction class is associated with broad scope and tolerates numerous functionalities, such as fluoro, chloro, bromo, iodo, trifluoromethyl, nitrile, ester, ether, and alkenyl, including heteroaryl - thiophene, benzothiophene, carbazolyl, indolyl, eugenol, and polycyclic cholesterol moieties. Detailed mechanistic investigations reveal that the reaction proceeds via iron-catalyzed N-O bond cleavage in N-methoxybenzamides, generating formaldehyde and benzamide, and through the intermediacy of isatin-ketimines and N-(hydroxymethyl)benzamides. Overall, this amidation reaction involves one C-C and two C-N bond-forming tandem processes, providing a range of beta-amino-aminomethyl-oxindoles (45 examples) in up to 88% yields. image
Keywords: benzamide; iron; Isatin; tandem amidation; tetrasubstituted carbon stereocenter

Ligand-free MnBr2-catalyzed chemo- and stereoselective hydroboration of terminal alkynes - Pawar, Rameshwar B.; Karmur, Mital H.; Punji, Benudhar (Chemistry-an asian jounrnal, 2024)
Developing simple and benign protocols for synthesizing alkenylboronates is crucial as they are synthetically valuable compounds in various organic transformations. In this work, we report a straightforward ligand-free protocol for synthesizing alkenylboronates via atom-economical hydroboration of alkynes with HBpin catalyzed by a manganese salt. The reaction shows a high level of chemo and regioselectivity for the terminal alkynes and exclusively produces E-selective alkenylboronates. The hydroboration scope is vast, with the resilience of a range of synthetically beneficial functionalities, such as halides, ether, alkenyl, silyl and thiophenyl groups. This reaction proceeds through the involvement of a metal-hydride intermediate. The developed alkenylboronate can be smoothly converted to useful C-C, C-N and C-I bond-forming reactions.
Keywords: alkenylboronates; alkyne; Hydroboration; manganese; stereoselectivity

Manganese-catalyzed chemoselective direct hydrogenation of α,β-epoxy ketones and α-ketoamides at room temperature - Shabade, Anand B.; Singh, Rahul K.; Gonnade, Rajesh G.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2024)
Chemoselective hydrogenation of alpha,beta-epoxy ketones and alpha-ketoamides is achieved at room temperature (25 degrees C) using 2.0 bar H-2 and a pincer-ligated Mn(I) catalyst that provides synthetically valuable alpha-hydroxy epoxides and alpha-hydroxy amides. This protocol applies to a wide range of alkyl- and aryl-substituted alpha,beta-epoxy ketones, including terpenes (alpha-ionone, nootkatone, and R-carvone)- and steroids (testosterone and progesterone)-derived epoxy ketones, and tolerates H-2 sensitive functionalities, such as halides, acetyl, nitrile, nitro, epoxide, alkenyl and alkynyl groups. Additionally, alpha-ketoamides bearing reducible functional groups, including acetyl and diazo benzene, were untouched under this protocol and selectively converted to alpha-hydroxy amides. A preliminary mechanistic study highlighted the metal-ligand cooperative H-2 activation process.
Keywords: alpha; beta-epoxy ketones; chemoselectivity; direct hydrogenation; manganese; Metal-ligand cooperation

Nickel-catalyzed branch-selective C-H alkylation of indoles and azoles with alkenes: an additive- and solvent-free approach - Ankade, Shidheshwar B.; Banerjee, Shuvajit; Punji, Benudhar (European Journal of Organic Chemistry, 2024)
The development of sustainable protocols for the synthesis of alkylated heteroarenes is crucial owing to their widespread existence in medicinally relevant and bioactive natural products. Herein, we describe an efficient, additive- and solvent-free approach for the regioselective C-H alkylation of indoles and azoles with alkenes using a nickel catalyst, which proceeds through a chelation-assistance strategy. The reaction exclusively provided branched alkylated products with the compatibility of alkyl, alkoxy, fluoro, trifluoromethyl, alkene, cyano, ester, and carbonyl groups. This protocol is applicable to other heteroarenes, such as imidazoles and benzimidazoles, providing the desired alkylated products with exclusive Markovnikov selectivity. The synthetic utility and scale-up of the reaction are demonstrated, and the protocol is in concord with the principles of green chemistry. Alkylation proceeds through facile and reversible C-H nickelation and alkene insertion processes, presumably involving rate-limiting reductive elimination. A straightforward nickel-catalyzed protocol for the C-H alkylation of indoles and azoles is disclosed that proceeds under additive- and solvent-free conditions. The reaction utilizes readily available alkenes as alkylating partners and delivers Markovnikov products with tolerance of sensitive functionalities. image
Keywords: Alkylation; branch selectivity; indoles; Nickel; solvent-free synthesis

Nickel-catalyzed chemodivergent coupling of alcohols: efficient routes to access α,α-disubstituted ketones and α-substituted chalcones - Bansal, Sadhna; Punji, Benudhar (Chemistry- a european journal, 2024)
Chemodivergent (de)hydrogenative coupling of primary and secondary alcohols is achieved utilizing an inexpensive nickel catalyst, (6-OH-bpy)NiCl2. This protocol demonstrates the synthesis of branched carbonyl compounds, alpha,alpha-disubstituted ketones, and alpha-substituted chalcones via borrowing hydrogen strategy and acceptorless dehydrogenative coupling, respectively. A wide range of aryl-based secondary alcohols are coupled with various primary alcohols in this tandem dehydrogenation/hydrogenation reaction. The nickel catalyst, along with KOtBu or K2CO3, governed the selectivity for the formation of branched saturated ketones or chalcones. A preliminary mechanistic investigation confirms the reversible dehydrogenation of alcohols to carbonyls via metal-ligand cooperation (MLC) and the involvement of radical intermediates during the reaction. The chemodivergent nickel-catalyzed approach provides alpha,alpha-disubstituted ketones from aryl-substituted secondary alcohols and benzyl alcohols via the borrowing hydrogen (BH) strategy in the presence of KOtBu, whereas exclusively alpha-substituted chalcones were accomplished in the presence of mild base K2CO3 through an acceptorless dehydrogenative coupling (ADC) strategy. image
Keywords: Alcohols; dehydrogenative coupling; Metal-ligand cooperation; Nickel; substituted carbonyl compounds

Atroposelective construction of biaryls enabled by a Ni(II)-catalyzed aerobic oxidation strategy - Pradhan, Chandini; Punji, Benudhar (ACS Central Science, 2025)
Enantioriched biaryls synthesis via aerobic oxidative cross-coupling of arenes involving <a class="ext-link" href="https://pubs.acs.org/doi/full/10.1021/acscentsci.4c01501" style="box-sizing: border-box; outline: none; text-decoration-line: none; color: rgb(51, 97, 184); transition: color 0.3s; font-family: Roboto, arial, sans-serif; font-size: 16px;">bioinspired oxygen activation by Ni(II).

CoBr2-catalyzed straightforward synthesis of quinoxalines via dehydrogenative coupling strategy - Dubey, Shivansh; Punji, Benudhar (Chemistry-an Asian Journal, 2025)
Establishing a benign and straightforward protocol for synthesizing biorelevant and synthetically valuable quinoxaline is very important. Herein, we report a simple and efficient protocol for the sustainable synthesis of diverse quinoxaline derivatives catalyzed by cobalt salt. The reaction proceeds through the dehydrogenative coupling of alkyl and aryl ethane 1,2-diols with aryl diamines in the presence of a catalytic CoBr2/K2CO3. The usage of the greener solvent 2-MeTHF and the release of H2 and H2O as the sole byproducts make the process advantageous. The protocol led to the synthesis of diverse quinoxalines bearing synthetically useful functionalities, such as fluoro, chloro, bromo, cyano, trifluoromethyl, and ether. The reaction is presumed to proceed via the dehydrogenative-condensation pathway involving a cobalt-hydride intermediate.
Keywords: cobalt; dehydrogenative coupling; heterocycles; ligand-free process; Quinoxaline

Hybrid pincer (PNN)Ni(II) complex catalyzed selective C-H alkylation of pyridones using unactivated alkyl chlorides - Verma, Suryadev K.; Samal, Pragnya Paramita; Pradhan, Chandini; Pandey, Dilip K.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2025)
The use of readily accessible unactivated alkyl chlorides in the alkylation reaction to install valuable alkyl and methyl motifs into privileged heterocycles is an underdeveloped area. Herein, we report the regioselective C-H alkylation of diverse pyridones employing challenging unactivated alkyl chlorides as coupling partners, enabled by a strategically developed quinolinyl-based pincer (Ph2PNNQ)Ni(II) complex. The air-stable nickel catalyst is highly effective for the selective alkylation of functionalized 2-pyridones with both primary and secondary alkyl chlorides as well as for the unexpected C6 methylation, furnishing a wide range of 6-alkyl-2-pyridone scaffolds (78 examples). Remarkably, the alkyls bearing biologically and pharmacologically significant motifs, such as pterostilbene, nonyl phenol, sesamol, estrone, vitamin E, stigmasterol, cholesterol, and diosgenin, were compatible under this catalytic approach. The insights into the mechanism suggest that the alkylation reaction follows a Ni(II)/Ni(III)/Ni(IV) pathway involving the crucial two-step, one-electron oxidative addition of alkyl chloride. Several control studies, kinetics, and EPR analyses were performed to understand the detailed reaction pathway, further supported by density functional theory calculations.
Keywords: alkyl chlorides; C-H/C-Cl activation; hybrid pincer ligand; Mechanism; Nickel; pyridones

Nickel-catalyzed regioselective C―H alkynylation of pyridones and isoquinolinones using alkynyl bromides - Verma, Suryadev K.; Patil, Harshal R.; Punji, Benudhar (ChemCatChem, 2025)
A straightforward and efficient protocol for the regioselective C & horbar;H alkynylation of 2-pyridones and isoquinolinones with bromoalkynes under nickel catalysis is described. The alkynylation reaction is enabled by a simple and inexpensive Ni(OTf)2/tBubpy catalyst system and uses easily accessible bromoalkynes. The protocol demonstrates a broad substrate scope with up to 95% yield (42 examples) and accommodates synthetically valuable functionalities, such as halides, trifluoromethyl, nitrile, ether, thioether, alkyl silanes, and alkene, as well as heteroarene moieties like pyridinyl, furanyl, and thiophenyl. The pyridinyl directing group on alkynylated 2-pyridones can be smoothly removed to give C6-alkynylated free NH-pyridone. Preliminary mechanistic studies suggest that the alkynylation proceeds via a 2e- oxidative addition pathway involving crucial C & horbar;H activation.
Keywords: alkynylation; C & horbar; H Activation; Mechanism; Nickel; pyridones

Palladium-catalyzed regioselective C(4)-H fluoroalkoxylation of indoles through weak chelation assistance - Vijaykumar, Muniyappa; Gonnade, Rajesh G.; Punji, Benudhar (ChemCatChem, 2025)
Installing fluoroalkyl motifs into biorelevant indoles is particularly interesting due to their ubiquitous presence in drug molecules. Herein, we demonstrate the regioselective C4 fluoroalkoxylation of indoles using fluoroalcohols via palladium-catalyzed chelation-assisted C & horbar;H activation. The weak chelating benzoyl moiety at the C3 position acts as a directing group for remote C(4)& horbar;H fluoroalkoxylation of diversely substituted indoles. This methodology demonstrates a high level of regioselectivity and tolerates a range of crucial functional groups, yielding diverse trifluoroalkoxylated indoles in moderate to good yields. Removal of directing/protecting groups and further functionalization established the synthetic utility of the methodology. A preliminary mechanistic investigation is conducted by isolating the palladacycle intermediate and performing the deuterium scrambling study. The regioselective C4 fluoroalkoxylation of indoles with various fluoroalcohols is achieved by the palladium-catalyzed weak chelation assistance strategy. The reaction is compatible for a range of important functionalities and proceeds via the intermediacy of a six-membered palladacycle following a Pd(II)/Pd(IV) pathway. image
Keywords: C-H activation; indoles; Palladium; Regioselective; Trifluoroalkoxylation

Regioselective difluoroalkylation of 2-pyridones with fluoroalkyl bromides enabled by a nickel(II) catalyst - Pradhan, Chandini; Khandelwal, Disha; Punji, Benudhar (Chemistry-An Asian Journal, 2025)
Regioselective C-H difluoroalkylation of diverse 2-pyridones with ethyl bromodifluoroacetates and bromodifluoroacetamides is accomplished by using a (dppf)NiCl2 catalyst under mild conditions. This efficient protocol could deliver a variety of C-3 difluoroalkylated pyridones with the tolerance of a range of highly susceptible functionalities, such as -Cl, -Br, -I, -COMe, -CN, -NMe2 and -NO2, including heteroarenes like pyridinyl, furanyl, thiophenyl and carbazolyl moieties. A preliminary mechanistic study suggests the radical pathway for the reaction involving fluoroalkyl radical intermediate.
Keywords: 2-pyridones; Difluoroalkylation; Nickel; radical intermediate; Regioselectivity

syn-Selective hydrosilylation and hydroboration of alkynes at room temperature catalyzed by a phosphine-free (NNN)Fe(ii) complex - Pradhan, Chandini; Dubey, Shivansh; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Punji, Benudhar (Catalysis Science & Technology, 2025)
Catalytic hydrofunctionalization of alkynes is the ideal and atom-economical route to synthesize vinylsilanes and vinylboronates, which are valuable organic building blocks. However, the process suffers from using expensive phosphine-ligated catalysts, sensitive organometallic activators, and elevated reaction temperatures. To overcome these challenges, herein, we developed a series of phosphine-free (NNN)-ligated iron complexes and demonstrated their potential as efficient catalysts for the hydrosilylation and hydroboration of both internal and terminal alkynes using NaOtBu as an activator. The reactions proceeded smoothly using 1.5 mol% catalyst loading at room temperature and provided syn-selective vinylsilanes and vinylboronates. This hydrofunctionalization exclusively delivered mono-silylated and mono-borylated vinyls with tolerance of sensitive functionalities. At the same time, terminal alkynes provided excellent anti-Markovnikov selectivity with thermodynamically feasible beta-(E)-vinylsilanes and beta-(E)-vinylboronates. The presence of an N-H moiety in the ligand backbone is crucial in generating an Fe(ii) active catalyst and facilitating the catalytic process. Mechanistic investigations, including controlled reactions and external additive experiments, were performed to propose a redox-neutral reaction mechanism with iron maintaining its +2 oxidation state throughout the cycle. The DFT energy calculations unanimously support the proposed reaction mechanism.